2014
DOI: 10.1093/jisesa/ieu066
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Binding of the PF2 Lectin to α-Amylase From Zabrotes subfasciatus (Coleoptera:Bruchidae) Larval Midgut

Abstract: Amylases are an important family of enzymes involved in insect carbohydrate metabolism that are required for the survival of insect larvae. For this reason, enzymes from starch-dependent insects are targets for insecticidal control. PF2 ( Olneya tesota ) is a lectin that is toxic to Zabrotes subfasciatus (Coleoptera: Bruchidae) larvae. In this study, we evaluated recognition of the PF2 lectin to α-amylases from Z. subfasciatus midgut and the effect of PF2 on α-amylase activity. PF2 caused a decrease of total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Additionally, PF2 lectin was able to recognize a number of soluble and membrane proteins in the Z. subfasciatus middle intestine during larval development. The PF2 lectin targets identified in Z. subfasciatus included α‐amylase, the V‐type proton ATPase, arginine kinase, prohibitin, polyubiquitin, actin, ATP‐dependent RNA helicase, ATP synthase subunit alpha, mitochondrial‐processing peptidase, α‐tubulin, the odorant receptor, and cytochrome c oxidase [15,16,20,21] . This suggests that these proteins could potentially mediate lectin toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PF2 lectin was able to recognize a number of soluble and membrane proteins in the Z. subfasciatus middle intestine during larval development. The PF2 lectin targets identified in Z. subfasciatus included α‐amylase, the V‐type proton ATPase, arginine kinase, prohibitin, polyubiquitin, actin, ATP‐dependent RNA helicase, ATP synthase subunit alpha, mitochondrial‐processing peptidase, α‐tubulin, the odorant receptor, and cytochrome c oxidase [15,16,20,21] . This suggests that these proteins could potentially mediate lectin toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The PF2 lectin targets identified in Z. subfasciatus included α-amylase, the V-type proton ATPase, arginine kinase, prohibitin, polyubiquitin, actin, ATP-dependent RNA helicase, ATP synthase subunit alpha, mitochondrial-processing peptidase, α-tubulin, the odorant receptor, and cytochrome c oxidase. [15,16,20,21] This suggests that these proteins could potentially mediate lectin toxicity. Thus, PF2 could interact with the orthologous receptors on human THP-1 cells.…”
Section: Pf2 Lectin Recognizes Thp-1monocytesmentioning
confidence: 99%
“…We previously reported that PF2 lectin is toxic to Z. subfasciatus larvae, and we identified several proteins from the midgut of Z. subfasciatus larvae that were specifically recognized by PF2 and thus could serve as potential targets for PF2 lectin insecticidal activity [11,12]. All the possible unigenes associated to these previously suggested PF2 targets were manually curated from the Z. subfasciatus transcriptome, which allowed us to identify a total of 30 different unigenes encoding putative PF2 lectin targets; of these, we were able to identify the complete open reading frame (ORF) for 8 sequences.…”
Section: Identification and Phylogenetic Analysis Of Potential Pf2 Lementioning
confidence: 90%
“…PF2 selectively recognizes complex triantennary tetrasialylated carbohydrates and binds structures in the midgut of Z. subfasciatus larvae [9]. We have hypothesized that the insecticidal mechanism involves PF2 interaction with glycoproteins essential for larval development [10], e.g., PF2 recognizes larval α-amylase and alters its biological function, however this cannot fully explain the insecticidal activity of PF2 because of the coexistence of non-glycosylated isoforms of larval amylases [11]. In addition, several potential targets of PF2 in the midgut of Z. subfasciatus larvae have been identified, including V-type proton ATPase, prohibitin, ATP-synthase subunit alpha, mitochondrial-processing peptidase, a growth factor-like glycoprotein, arginine kinase, polyubiquitin, actin, ATP-dependent RNA helicase, α-tubulin, odorant receptor, cytochrome c oxidase, mitochondrial, sensorial, structural, and defense proteins, and proteins involved in the electron transport chain [12,13].…”
Section: Introductionmentioning
confidence: 99%